La mujer en la legislación de Adriano - Pavón Torrejón, Pilar (Studia et documenta historiae et iuris, 2016)
This article analyzes Hadrian´s various legal provisions linked to femenine world. Firstly, it is noted the level of attention dedicated to woman within the legislative policy of that Emperor. On the other hand, it allows to study the social reality and legal issue about women during those years.